An Overview of Systematic Reviews of Ginkgo biloba Extracts for Mild Cognitive Impairment and Dementia - Zhang, Hong-Feng; Huang, Li-Bo; Zhong, Yan-Biao; Zhou, Qi-Hui; Wang, Hui-Lin; Zheng, Guo-Qing; Lin, Yan (Frontiers in Aging Neuroscience, 2016)
Ginkgo biloba extracts (GBEs) have been recommended to improve cognitive function and to prevent cognitive decline, but earlier evidence was inconclusive. Here, we evaluated all systematic reviews of GBEs for prevention of cognitive decline, and intervention of mild cognitive impairment (MCI) and dementia. Six databases from their inception to September 2015 were searched. Ten systematic reviews were identified, including reviews about Alzheimer’s disease (n=3), about vascular dementia (n=1), about both Alzheimer’s disease and vascular dementia (n=2), about Alzheimer’s disease, vascular dementia and mixed dementia (n=3), and a review about MCI (n=1). Based on the overview quality assessment questionnaire, eight studies were scored with at least 5 points, while the other two scored 4 points and 3 points, respectively. Medication with GBEs showed improvement in cognition, neuropsychiatric symptoms, and daily activities, and the effect was dose-dependent. Efficacy was convincingly demonstrated only when high daily dose (240mg) was applied. Compared with placebo, overall adverse events and serious adverse events were at the same level as placebo, with less adverse events in favor of GBE in the subgroup of Alzheimer's disease patients, and fewer incidences in vertigo, tinnitus, angina pectoris, and headache. In conclusion, there is clear evidence to support the efficacy of GBEs for MCI and dementia, whereas the question on efficacy to prevent cognitive decline is still open. In addition, GBEs seem to be generally safe.